Analysis of SMARCA4 and SMARCA2 Loss in Lung Sarcomatoid Carcinomas - Halide Nur URER; Nurcan UNVER; Neslihan FENER (Federation of Turkish Pathology Societies, 2023)
Objective: Sarcomatoid carcinomas of the lung are a group of aggressive tumors. It has been reported that losses of SMARCA4 and SMARCA2, which play a role in the repair and remodeling of chromatin, contribute to the initiation, progression, and differentiation of neoplasms. The aim of our study was to examine SMARCA4 and SMARCA2 profiles in sarcomatoid carcinomas of the lung. Material and Method: We screened pleomorphic carcinomas (PCs), carcinosarcomas (CSs), and pulmonary blastomas (PBs). The loss of SMARCA4 and SMARCA2 expression in the tumors was evaluated using immunohistochemical methods. The tumors were also examined to determine immunophenotype, histological tumor diagnosis, surgical resection, tumor histological component, largest tumor diameter, and lymph node metastasis status. Results: Sixty-nine cases were screened, of which 84% were PCs, 13% were CSs, and 2.8% were PBs. In PCs components, 84.4% were biphasic and 15.5% were monophasic. The PCs showed the most frequent loss of SMARCA4 (25.8%) and SMARCA2 (44.8%). A loss of SMARCA4 and SMARCA2, respectively, was detected in 14.2% and 24.4% in both components of biphasic PCs; 12.2% and 14.2% in the sarcoma component of biphasic PCs; 0% and 8.1% in the carcinoma component of biphasic PCs; 22.2% and 33.3% in monophasic PCs; 0% and 22.2% in both components of CSs; and 0% and 22.2% in the sarcoma component of CSs. Conclusion: These findings demonstrate a loss of expression of SMARCA4 and SMARCA2 in pulmonary sarcomatoid carcinomas. Loss of the SMARCA complex may be caused by the heterogeneous morphological profile of sarcomatoid carcinomas, independent of tumor histopathological parameters.